Islamist Party, Electoral Politics and Da‘wa Mobilization among Youth: The Prosperous Justice Party (PKS) in Indonesia - Noorhaidi, Hasan (2016)
The involvement of the Prosperous Justice Party (PKS, Partai Keadilan Sejahtera) in the electoral democratic system in Indonesia raises a question whether it is possible for a political party with a deeply religious ideology to liberalize and entertain democracy? The decision to enter politics not infrequently entails an abandonment of ideological purity. It represents an acceptance of the political order and power sharing-based politics. While identity and ideology are instrumental in political mobilization for PKS, it has no choice but to negotiate and interact with other political actors through coalitions and parliamentary politics. A modern party involved in a competitive and rule-based system, it is also required to broaden its electorate and reach out to non-Islamist voters. It is intriguing in this context to explore the party’s strategy to maintain its Islamist platforms and the base of support while allying itself with distinctly non-Islamist ruling elites, and engage in the pragmatic ruling coalition. Understanding the paradoxical roles of an Islamist party when involved in the ongoing electoral democratic process, this paper also looks at the future of political Islam in Indonesia.